Impact of imperceptible motion delay in avatar head movement away from a target on preference formation - Zixiang Yue; Yoshihiro Nakata; Hiroshi Ishiguro (PLoS ONE, 2025)
This study investigated the effect of imperceptible motion delay in avatar head movements on preference formation among operators. Despite the growing importance of avatars in various applications, there is a notable lack of research on how subtle manipulations of avatar movements influence operator cognition and decision-making. By aligning the head and gaze directions, we developed a virtual avatar system designed to subtly manipulate the operator’s attention toward specific objects using motion delay. The experimental results revealed that operators tend to prefer objects presented without motion delay, suggesting a negative effect of motion delay on preference formation. These findings highlight motion delay as a significant factor in directing attention and shaping preferences in virtual environments, which have implications for enhancing user experience and optimizing human–computer interaction design. It also emphasizes the necessity of protective measures in avatar-based systems to guard against subtle influences and underscores the ethical and security concerns related to these technologies.